Escribimos textos con signos de interrogación y admiración - Montero Bernal, Yheny Rosario (2019)
The session entitled Written texts with signs of interrogation and admiration, was developed in the area of Communication, taking into account the competence writes various types of texts in their mother tongue, from the necessary resource as the ability uses written language conventions in a way relevant, it has been possible to achieve in students the performance uses grammatical resources (signs of admiration and questioning) and spelling (capital letters and the end point) that contribute to make sense of your text. Use rhetorical formulas to mark the beginning and end of the sentences you write._x000D_ In the course of the session, motivational and challenging activities were applied that encouraged the children to write a short text where they express emotions with signs of admiration and question marks about the customs and traditions of our country._x000D_ The pedagogical processes such as motivation and exploration of previous knowledge, problematization, construction of learning and information processing, evaluation and transfer in the didactic processes of the area were taken into account._x000D_ The learning strategies were consistent with the interests and needs of students in third grade of primary education.